Effect of Immunomodulators and Antibiotic on Haematological Profile of Gir Cows with Subclinical Endometritis - Parikh, Suryakant S.; Kavani, Fulabhai S.; Savsani, Harish H.; Vasava, Amrita A.; Savaliya, Bhagvanji D. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The present study was aimed to assess the influence of immunomodulators and antibiotic on haematological profile in subclinical endometritis (SCE) affected Gir cows. Forty-eight apparently healthy Gir cows at 40-60 days postpartum, 4 to 8 years old, were randomly selected from an organized dairy farm. All the postpartum cows with (n=40) or without (n=8) subclinical endometritis were screened using cytobrush technique. Subclinical endometritis affected cows were randomly divided into 5 groups (8 animals/group). In Group A, Escherichia coli LPS (100 µg in 30 mL PBS once i/u), in Group B, oyster glycogen (500 mg in 30 mL PBS once i/u), in Group C, levofloxacin (30 mL for three consecutive days i/u), in Group D, garlic extract (5 mL in 30 mL distilled water for three consecutive days i/u) was used, while Group E (positive control) did not receive any treatment and was allowed for self-cure. A group of normal healthy cows (n=8) served as negative control (Group F). Blood samples were collected at estrus before treatment (0 h) and after treatment (72 h and at subsequent estrus) and compared for changes in haematological parameters. The results revealed significantly (P <0.05) decreased haemoglobin, packed cell volume, lymphocyte, eosinophil, and increased total leukocyte count and neutrophil counts in SCE affected cows as compared to healthy control group. After 72 h of treatment and at subsequent estrus, the values of TLC decreased significantly (P <0.05), whereas the Hb and PCV increased significantly (P <0.05) in all the SCE groups. The conception rates at subsequent estrus were relatively higher with E. coli LPS (50.00%) and oyster glycogen (37.50%), at par with a control group (37.50%), than antibiotic and garlic treated groups (25.00% each), and nil in the positive control group. The immunomodulators were thus the drugs of choice for treatment of postpartum subclinical endometritis with improved haematological profile and conception rate in Gir cows.